Suplementação com levedura de Crômio eleva a concentração sérica de Crômio em bovinos - Giometti, José; Chiacchio, Simone Biagio [UNESP]; Albas, Avelino; Pardo, Paulo Eduardo; Bremer Neto, H.; Giometti, Ana Ines; Reis, Luis Souza Lima Souza [UNESP] (SciELO Espana/Repisalud, 2011)
This study evaluated the effect of daily chromium supplementation at growing doses on serum Cr levels in cattle. Sixty Nellore heifers 2 to 5 years old were randomly assigned to one of four groups (15 heifers/group) fed non-fertilized Brachiaria decumbens pasture. In the control group (Gc), the heifers received a mineral mixture without Cr. In the other groups, heifers received 0.59, 1.19 or 2.38 mg Cr+3/animal/day, groups G8,5, G17 and G34, respectively. Blood samples were collected on days 0, 30 and 60. Serum concentration of chromium was determined by graphite furnace atomic absorption spectrophotometer. The chromium source used was the chromium yeast. The results do not support any significant difference (p>0.05) among serum chromium levels of heifers in groups Gc, G8,5, G17 and G34 at a same observation day. Only effect of supplementation time was detected in group G34. In this group there was significant increase (p<0,05) in the concentration serum chromium 60 days after the beginning of the experiment. Concluded Cr yeast can be used as the source of this mineral element for animals and supplementation with 2.38 mg/ cattle/day was the dose that most increased the serum concentration of Cr in Nellore cattle during the experimental period.

O estudo avaliou o efeito da suplementação com doses crescentes de crômio/dia sobre a concentração sérica de Cr em bovinos. Sessenta novilhas da raça Nelore com idade entre 2 e 5 anos foram distribuídas aleatoriamente em 4 grupos (15 novilhas/grupo) alimentadas com pastagem de Brachiaria decumbens não fertilizada. No grupo controle (Gc), as novilhas receberam mistura mineral sem adição de Cr. Nos demais as novilhas receberam 0,59; 1,19 e 2,38 mg de Cr+3/animal/dia (grupos G8,5, G17 e G34, respectivamente). Colheramse amostras de sangue nos dias 0, 30 e 60. A concentração sérica de crômio foi determinada por meio de espectrofotometria de absorção atômica com forno de grafite. A fonte de crômio utilizada foi a levedura de crômio. Os resultados mostram que não houve diferença significativa (p>0,05) na concentração sérica de crômio das novilhas entre os grupos G8,5, G17 e G34, num mesmo dia de observação. O único efeito observado foi do tempo de suplementação com crômio no o grupo G34. Neste grupo a concentração sérica de crômio apresentou aumento significativo (p<0,05) 60 dias após o início da suplementação. Conclui-se a levedura de Cr pode ser utilizada como fonte deste elemento mineral para os bovinos e a suplementação com 2,38 mg/bovino/dia foi a dose que mais elevou a concentração sérica de Cr nos bovinos da raça Nelore durante o período experimental.
Supplementation with chromium yeast increase serum concentration of chromium in cattle
Keywords: Mineral supplementation; Suplementação mineral